REPRODUCTIVE HEALTH IN RICKSHAW DRIVERS: Occupational Exposure to Environmental Stressor - Nabi, Ghulam; Amin, Muhammad; Khan, Ayaz Ali (BALI MEDICAL JOURNAL, 2014)
Background: In urban environment, exposure to the emission of motor vehicles is common. In urban peoples it is a very difficult task to distinguish among peoples with different grades of momentous period exposure to such pollutants. Objective: The objective of this study was to determine the effects of diesel exhaust, gasoline emission, Particulate Matter (PM) noise and heat on the reproductive health of rickshaw drivers. Methods: Adult married male individuals were recruited randomly in the study from Btkhella, Malakand agency, Khyber Pakhtunkhwa, Pakistan. Two groups were made, control (n=45) and rickshaw drivers (n=50). A special questionnaire was designed about occupational activities, socio-demographic and clinical characteristics. From both groups 5 mL of the blood was collected and was analyze for serum total testosterone and cortisol using Biocheck (USA) and Antibodies-online GmbH (Germany) kits. Results: In control group the Mean±SEM of total serum testosterone was 657.6±16.84 ng/dl and cortisol was 443.8±14.67 mU/L. In rickshaw drivers the Mean±SEM of total serum testosterone was 577.1±11.42 ng/dl and cortisol was 595.1±8.879mU/L. In rickshaw drivers there was a significant reduction in total serum testosterone (P 0.0002) but a significant increase in serum cortisol level (P < 0.0001) at 95% confidence interval. Conclusions: Reproductive health problems like decreased libido, erectile dysfunction, absent morning and nocturnal erection, ejaculatory problems, primary infertility and secondary infertility were prevalent in rickshaw drivers but, no such problems were found in control group. Chronic exposure to pollutants such as diesel exhaust, gasoline emission, Particulate Matter (PM) noise and heat negatively regulate Hypothalmo-Pituitary Gonadal axis (HPG) leading to reproductive problems.